Can I trust them to do everything? The role of distrust in ethics committee consultations for conflict over life-sustaining treatment among Afro-Caribbean patients. Issue 9 (13th May 2016) - Romain, Frederic; Courtwright, Andrew
Abstract : Background: Distrust in the American healthcare system is common among Afro-Caribbeans but the role of this distrust in conflict over life-sustaining treatment is not well described. Objective: To identify the ways that distrust manifests in ethics committee consultation for conflict over life-sustaining treatment among Afro-Caribbean patients. Methods: This was a retrospective cohort study at a large academic hospital of all ethics committee consultations for life-sustaining treatment among Afro-Caribbean patients and their surrogates. We reviewed medical records and identified cases in which ethics consultants described distrust as playing a role in the conflict over life-sustaining treatment. Results: Of the 169 ethics committee consultation cases for conflict over life-sustaining treatment, 11 (6.5%) involved patients who self-identified as Afro-Caribbean. Distrust played a role in several of these cases, with surrogates of three patients, in particular, illustrating the way that perceived heath disparities, past labelling and concerns about continued maltreatment generated distrust leading to conflict over life-sustaining treatment. Conclusions: Exploring issues of distrust may help ethics consultants identify the source of conflict over life-sustaining treatment among Afro-Caribbean patients.